Analysis of immune cells draining from the abdominal cavity as a novel tool to study intestinal transplant immunobiology - Meier, Dominik (2010)
Summary During intestinal transplant (ITx) operation, intestinal lymphatics are not reconstituted. Consequently, trafficking immune cells drain freely into the abdominal cavity. Our aim was to evaluate whether leucocytes migrating from a transplanted intestine could be recovered from the abdominal draining fluid collected by a peritoneal drainage system in the early post-ITx period, and to determine potential applications of the assessment of draining cellular populations. The cell composition of the abdominal draining fluid was analysed during the first 11 post-ITx days. Using flow cytometry, immune cells from blood and draining fluid samples obtained the same day showed an almost complete lymphopenia in peripheral blood, whereas CD3+CD4+CD8 -, CD3+CD4-CD8+ and human leucocyte antigen D-related (HLA-DR)+CD19+ lymphocytes were the main populations in the draining fluid. Non-complicated recipients evolved from a mixed leucocyte pattern including granulocytes, monocytes and lymphocytes to an exclusively lymphocytic pattern along the first post-ITx week. At days 1-2 post-Itx, analysis by short tandem repeats fingerprinting of CD3 +CD8+ sorted T cells from draining fluid indicated that 50% of cells were from graft origin, whereas by day 11 post-ITx this proportion decreased to fewer than 1%. Our results show for the first time that the abdominal drainage fluid contains mainly immune cells trafficking from the implanted intestine, providing the opportunity to sample lymphocytes draining from the grafted organ along the post-ITx period. Therefore, this analysis may provide information useful for understanding ITx immunobiology and eventually could also be of interest for clinical management.